CELAC: Mexican Foreign Policy Interest on Latin American and Caribbean Regionalism - Kusumaningrum, Demeiati Nur (Global: Jurnal Politik Internasional, 2019)
La Comunidad de Estados Latinoamericanos y Caribeños (CELAC) was initiated in 2011 as a forum for dialogue and consensus between Latin American and Caribbean governments where it forms a trading block that excludes the United States and Canada. The US objected to the establishment of CELAC which seemed to challenges the former regional organization (OAS). This paper aims to analyze the considerations of the Mexican government to join CELAC in the midst of mutual agreement with US and NAFTA. Theory of formulation of foreign policy is used to answer the sources of political consideration of the Mexican government. It is a qualitative descriptive research that used primary data comes from Mexican government reports, content of CELAC official website, and journals. Data is obtained from library research. The analysis technique is carried out through generalization of the evidence and organization of the data so that it presents a coherent and consistent picture in proving the basic assumptions of the theory. It examines determinant of Mexico foreign policy formulation include 1) expansion of FTA in order to raise national economy, 2) maintaining the legitimacy of the government through multilateral cooperation, 3) identity politics as a Latin American, 4) increasing state performance in dealing with eradication of drugs and immigrant problems, 5) state economic revival post 2008 global crisis, 6) CELAC as a bridge to expand bi-regional trade with the European Union, and 7) forum to balance US dominant interest in the region.